Clec12A, CD301b, and FcγRIIB/III define the heterogeneity of murine DC2s and DC3s - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Heger, Lukas; Lächele, Lukas; Tochoedo, Nounagnon Romaric; Kaszubowski, Tomasz; Hatscher, Lukas; Baranska, Anna; Tchitashvili, Giorgi; Nimmerjahn, Falk; Lehmann, Christian; et al. (Cell Reports, 2024)
Over the last decade, multiple studies have investigated the heterogeneity of murine conventional dendritic cells type 2 (cDC2s). However, their phenotypic similarity with monocytes and macrophages renders their clear identification challenging. By creating a protein atlas utilizing multiparameter flow cytometry, we show that ESAM+ cDC2s are a specialized feature of the spleen strongly differing in their proteome from other cDC2s. In contrast, all other tissues are populated by Clec12A+ cDC2s or Clec12A− cDC2s (high or low for Fcγ receptors, C-type lectin receptors, and CD11b, respectively), rendering Clec12A+ cDC2s classical sentinels. Further, expression analysis of CD301b, Clec12A, and FcγRIIB/III provides a conserved definition of cDC2 heterogeneity, including the discovery of putative FcγRIIB/III+ DC3s across tissues. Finally, our data reveal that cell identity (ontogeny) dictates the proteome that is further fine-tuned by the tissue environment on macrophages and dendritic cells (DCs), while monocytes and plasmacytoid DCs (pDCs) display subset intrinsic default settings.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CD301b; CP: Immunology; DC3; dendritic cells; heterogeneity; macrophages; monocytes; mouse; myeloid cells; proteome atlas; subpopulations